The Healing Power of Teacher-Student Relationships in Repairing Childhood Abuse: Commonalities and Differences with Clinical Social Work Practice - Mehak Jamil (International Journal of School Social Work, 2022)
Research indicates survivors of childhood abuse are able to form the same quality relationships with teachers as non-abused children (Armstrong, Hasket & Hawkins, 2017). However, there is little research indicating what factors within the teacher-student relationship help build this resiliency. This study looks to clinical social work practice as a basis for understanding what qualities of the therapeutic relationship can extend to or overlap with non-clinical relationships with students who have a trauma history, within the teaching field. To better understand experiences within these relationships, semi-structured interviews were conducted with both a clinical social worker who has teaching experience at the post-secondary level, and the study enlisted the researcher as a participant to ascertain the student/ client perspective. Effectively a researcher self-study, findings indicated qualities of safety, empathy and client/student empowerment, albeit in different ways, helped to correct and repair some of the damage of childhood abuse within both therapeutic and teacher-student relationships.
Keywords: trauma; child abuse; teacher-student relationships; school mental health; school social work